2015
DOI: 10.1097/ccm.0000000000000747
|View full text |Cite|
|
Sign up to set email alerts
|

Patients’ Perspectives of Enrollment in Research Without Consent

Abstract: Objective Research in acute illness often requires an exception from informed consent (EFIC). Few studies have assessed the views of patients enrolled in EFIC trials. This study was designed to assess the views of patients and their surrogates of EFIC enrollment in a randomized, placebo-controlled trial of an investigational agent for traumatic brain injury. Design Interactive interview study. Setting Nested within the Progesterone for the Treatment of Traumatic Brain Injury (ProTECT III) trial, a Phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The distinction between making a recommendation for others and stating personal preferences has been observed in other contexts, including emergency research conducted under the exception from informed consent. 2931 While some individuals “crossed over” in both directions, these data demonstrate a tendency to recommend more extensive consent processes when making decisions for others in the IRB role. This tendency is understandable and well-intentioned.…”
Section: Discussionmentioning
confidence: 82%
“…The distinction between making a recommendation for others and stating personal preferences has been observed in other contexts, including emergency research conducted under the exception from informed consent. 2931 While some individuals “crossed over” in both directions, these data demonstrate a tendency to recommend more extensive consent processes when making decisions for others in the IRB role. This tendency is understandable and well-intentioned.…”
Section: Discussionmentioning
confidence: 82%
“…With only a one-line description of a future, hypothetical study, participants may have been less comfortable supporting deferred consent. Previous studies have also found discrepancies between support for specific versus open-ended or hypothetical research studies [16, 17]. Second, in the description of the future, hypothetical study, we did not specify that the option for deferred consent would apply only to subjects who lack capacity.…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration is that studies assessing attitudes towards deferred consent often fail to distinguish views of patients and surrogates. For example, the finding that there is less acceptability from ethnic minority groups incorporates both surrogate-decision makers and previously incapacitated patients (an under-served group) with no distinction between them [42,43]. The lack of clarity between these groups risks inaccurately over-representing minority views, further raising the issue of intersectionality whereby incapacitated patients are already likely to be under-served in deferred consent research.…”
Section: Discussionmentioning
confidence: 99%